Effects of feeding dietary Palm Kernel Cake on egg production and egg quality of Khaki Campbell duck - Samsudin, Anjas Asmara @ Ab Hadi; Hendry, Nickcarlstann; Khaing, Khin Thida (Scienceline Publication, 2016)
The study examined the effects of graded levels of Palm Kernel Cake (PKC) on the laying performance and egg quality in Khaki Campbell ducks. Twenty-seven female Khaki Campbell ducks were randomly assigned to three dietary treatments viz T1 (0% PKC; control), T2 (15% PKC) and T3 (35% PKC) and the performance characteristics and egg quality traits were examined for 4 weeks. Ducks fed T2 and T3 had higher (P0.05) on the feed conversion ratio in ducks. Similarly, dietary PKC did not affect (P>0.05) the weekly egg production and the percentage of hen-day production. Ducks fed T2 and T3 had greater (P0.05) by dietary PKC. Results indicated that Khaki Campbell ducks could tolerate up to 35% PKC in their diets without detrimental effects on egg production and egg quality.